Tata Kelola Perusahaan Memoderasi Hubungan Corporate Social Responsibility dan Kinerja Keuangan - Susanto, Androni; Fiona, Fiona (E-Jurnal Akuntansi; Vol 32 No 10 (2022), 2022)
Corporate social responsibility (CSR) is closely related to company performance. The study aims to investigate whether corporate governance moderates the relationship between corporate social responsibility (CSR) and corporate financial performance. The research population is manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The sampling method used was purposive sampling. The data analysis tool used is Moderate Regression Analysis (MRA). The results of the analysis show that corporate social responsibility (CSR) has a positive effect on financial performance. The independent board of commissioners and commissioners strengthen the relationship of corporate social responsibility (CSR) and corporate performance. Meanwhile, foreign ownership weakens the relationship between corporate social responsibility (CSR) and company performance. Government ownership does not act as a moderating variable on the relationship between corporate social responsibility (CSR) and company performance. Keywords: Financial Performance; Corporate Social Responsibility; Board of Commissioners; Foreign Ownership; Government Ownership.